Peranan Keluarga dan Masyarakat dalam Membentuk Etika Anak Remaja di Kecamatan Simpang Pematang Kabupaten Mesuji - Suci Artha, Purawa (Samsara Institute Publisher, 2025)
Ethics refers to intention whether an action may be carried out or not depends on the consideration of good or bad intentions and their consequences. Ethics is rooted in one’s conscience, reflecting how individuals should behave ethically and appropriately based on their personal awareness. However, the community in Simpang Pematang District pays little attention to the ethical development of children, and the overall ethical behavior of adolescents tends to be poor. This situation encouraged the researcher to conduct a study addressing the following questions: What is the ethical condition of adolescents? Does the family environment influence the formation of adolescents’ ethics? And does the community environment influence the development of adolescents’ ethics? The study aimed to examine the influence of both the family and community environments on the ethics of adolescents in Simpang Pematang District, Mesuji Regency. The research was conducted among all Hindu families in the district, with the population consisting of all Hindu households with adolescent children, totaling 60 families. A sample of 30 respondents from Wira Bangun Village, Simpang Pematang Village, and Sido Rukun Village was selected using simple random sampling. The instrument used was a questionnaire containing 30 items. This quantitative research was analyzed using the Product Moment correlation test at a 5% significance level. The results show that the ethical condition of adolescents, based on assessments from both adolescents and parents, ranged from 2.99 to 3.01 for adolescents and 2.75 to 3 for parents. Furthermore, there is a positive influence between the family environment and adolescents’ ethics, with a correlation value of r = 0.85 greater than 0.25, and similarly, a positive influence between the community environment and adolescents’ ethics, also with a correlation value of r = 0.85 greater than 0.25. It is recommended that families provide good examples of behavior to their children, and that peers become role models for the younger generation so they do not fall into behaviors that violate societal norms in Indonesia.